1999
DOI: 10.1073/pnas.96.16.8849
|View full text |Cite
|
Sign up to set email alerts
|

Potent urea and carbamate inhibitors of soluble epoxide hydrolases

Abstract: The soluble epoxide hydrolase (sEH) plays a significant role in the biosynthesis of inf lammation mediators as well as xenobiotic transformations. Herein, we report the discovery of substituted ureas and carbamates as potent inhibitors of sEH. Some of these selective, competitive tightbinding inhibitors with nanomolar K i values interacted stoichiometrically with the homogenous recombinant murine and human sEHs. These inhibitors enhance cytotoxicity of transstilbene oxide, which is active as the epoxide, but r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
282
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 233 publications
(296 citation statements)
references
References 30 publications
(48 reference statements)
14
282
0
Order By: Relevance
“…This enzyme, which represents a single known and highly conserved gene product with over 90% homology between rodent and human (30), can be inhibited selectively and competitively in vitro by a variety of urea, carbamate, and amide derivatives (16,18). We have shown that injection of one such inhibitor, DCU, into spontaneously hypertensive rats resulted in a lowering of blood pressure.…”
Section: Discussionmentioning
confidence: 93%
“…This enzyme, which represents a single known and highly conserved gene product with over 90% homology between rodent and human (30), can be inhibited selectively and competitively in vitro by a variety of urea, carbamate, and amide derivatives (16,18). We have shown that injection of one such inhibitor, DCU, into spontaneously hypertensive rats resulted in a lowering of blood pressure.…”
Section: Discussionmentioning
confidence: 93%
“…The possibility that inhibition of sEH with AUDA would alter the production of HEETAs and THETAs was tested with sEH inhibitors AUDA or CDU (31,32). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Aortic rings were incubated with [ 14 C]AA as described above in the presence or absence of a sEH inhibitor, AUDA (10 Ϫ6 M) (31,32). The incubation buffer was transferred immediately into 25 volumes of methanol acidified with a volume of glacial acetic acid that would acidify the aqueous solution to pH 3.5.…”
Section: Methodsmentioning
confidence: 99%
“…The free acid AUDA and its n-butyl ester are both highly potent as inhibitors of the recombinant, affinity-purified murine and human sEHs (Morisseau et al 1999. Both compounds are high melting lipophilic solids and thus difficult to formulate.…”
Section: Discussionmentioning
confidence: 99%
“…While sEH initially was thought to be only involved in xenobiotic metabolism, it has been well established that fatty acid epoxides are excellent substrates for this enzyme (Zeldin et al 1993). Several classes of inhibitors have been developed for the enzyme, the most notable based on the 1,3-disubstituted urea pharmacophores (Morisseau et al 1999. The finding that sEH −/− mice are viable (Sinal et al 2000) suggests that serious side effects from the therapeutic use of sEH inhibitors are minimal.…”
Section: Introductionmentioning
confidence: 99%